FIRE RETARDANT PROPERTIES OF POLYESTERSULFONE KETONES (American Journal of Pedagogical and Educational Research, 2024)
Currently, a large number of methods for the synthesis of block copolymers make it possible to combine an unlimited number of different molecules and synthesize a large number of block copolymers. The thermal and mechanical properties and stability of the synthesized block copolymers vary widely. Newly synthesized block copolymers and copolymers can be used as heat-resistant structural and film materials in various fields of modern industry (automotive, electronics, electrical, aviation, chemical industries).